The relationship of some biochenmatic variables with accuracy and speed of transmission The serves of the Premier League players in volleyball - بان فيصل احمد (الرياضة المعاصرة)
The problem of research is reflected by the importance of the skill of overwhelming transmission, in the level of the results of the international teams advanced, which is one of the modern offensive tactics, the Iraqi league teams lack the effectiveness of this skill in the players and also the same to our national teams that rely on sources of players on The Iraqi league and the extent of its strength, through which the researcher work study based on biochemical analysis in addition to the accuracy and speed of the ball, in order to extract the best variables that have an effective role in these skills, which consequently represent training variables by specialists on the status The aim of the research is to identify the values ​​of some biochemical variables and the accuracy and speed of the overwhelming transmission skills of the Iraqi Premier League clubs in the volleyball season. (2016-2017), and the type of relationship between the variables biochemistry under study and the accuracy and speed of the skill of overwhelming transmission, and used the descriptive method descriptive method of the researcher and the sample of the study of players who know the skill of overwhelming transmission, Iraqi Premier League Volleyball Championship (2016-2017) m. The players in the Premier League did not possess the high level of skill in the performance of the overwhelming transfer, because most of the search variables gave a reverse index with accuracy and speed of skill, and concluded that the player man has the greatest impact in the accuracy and speed of skill of other variables, and recommended the need to confirm the trainers on the technical and physical requirements of the transmitter Overwhelming for its importance in the technical vehicles and modern planning of the game.